Analisis Karakteristik Campuran Aspal AC–WC Menggunakan Filler Silika untuk Meningkatkan Stabilitas dan Kelelehan - Subhan Mulyana; Ida Farida; Rifki Ripaldi (Jurnal Konstruksi, 2026)
Early pavement damage is often caused by non-optimal asphalt mix composition, particularly related to filler selection. This study analyzes the effect of partial substitution of stone ash filler with silica (SiO2) on the Marshall characteristics of AC-WC asphalt mixtures using a quantitative experimental method. Marshall testing was conducted with silica contents of 0%, 2%, 4%, and 6% at an Optimum Asphalt Content of 6.3%, referring to the 2018 Bina Marga Specifications. The results show that silica contents of 2% and 4% satisfy all Marshall parameters, with stability values of 1011 kg and 950 kg, flow values of 2.97 mm and 3.43 mm, VIM of 3.62% and 4.17%, VMA of 16.22% and 16.70%, VFB of 78.88% and 79.26%, and MQ of 340.89 kg/mm and 276.72 kg/mm, respectively. The main contribution of this study is the identification of an overfilling mechanism at silica contents >=6% that leads to reduced stability. Practical implications indicate a potential material cost savings of 15-20% and the feasibility of silica as an alternative renewable filler, although durability performance (IKS of 89.28% and 69.91%) still requires improvement through anti-stripping treatment for long-term applications.